Orodispersible tablets: An overview - Bandari, Suresh; Mittapalli, Rajendar Kumar; Gannu, Ramesh (Asian Journal of Pharmaceutics (AJP), 2014)
Oral drug delivery remains the preferred route for administration of various drugs. Recent developments in the technology have prompted scientists to develop orally disintegrating tablets (ODTs) with improved patient compliance and convenience. ODTs are solid unit dosage forms, which disintegrate or dissolve rapidly in the mouth without chewing and water. Orally disintegrating tablets provide an advantage particularly for pediatric and geriatric populations who have difficulty in swallowing conventional tablets and capsules.This review describes the various formulation aspects, disintegrants employed and technologies developed for ODTs, along with various excipients, evaluation tests, marketed formulations, and drugs explored in this field.